Examining the utility of an extended theory of planned behavior (TPB) on academic dishonesty among undergraduates - Moshood Imran, Adesile; Hussien, Suhailah; Alaraimi, AIsha Salim (Springer Netherlands, 2024)
This cross-sectional study investigated the efficacy of an extended theory of planned behavior in predicting academic dishonesty among students of higher education. The participants comprised 328 undergraduates drawn from Nigerian and Malaysian public universities. Existing measures were adapted and validated using Cronbach’s alpha statistics and confirmatory factor analysis approach. The fit statistics of the extended model (χ2/df = 2.08, CFI = .926, and RMSEA = .057) were adequate. Findings revealed that academic dishonesty, especially cheating, was common in the sampled population. The key psychological factors contributing to this problem were positive attitude towards the conducts, lack of strict sanctions against the conducts, and a perceived self-confidence of some students to cheat successfully. Another strong factor was the belief that intellectual material is “public property.” The modified model was not gender-bias, suggesting that the underpinning factors were similar irrespective of the gender-type of the students. Hence, a unified, non-gender discriminating approach will be effective in planned actions towards reversing the trend.